Analysis Of The Influence Of Behavioral Intention, Perceived Ease Of Use And Perceived Usefulness On Actual Usage Of Digital Wallet Customers - Bahtiar Efendi; Silvia Ekasari; Indra Sani; Esti Nur Wakhidah; Musran Munizu (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
This study aims to ascertain whether perceived utility, perceived ease of use, and behavioral intentions affect actual use. The study's subjects were e-wallet users from Indonesia. This study employed objective observation as a non-probability sampling method. Users of e-wallets who had completed at least one transaction made up the study sample. The researchers selected a sample of one hundred people. Questionnaires are used to collect research data. Information from a questionnaire that was given to participants as part of the descriptive data analysis procedure was used in this study. The researchers employed multiple regression analysis techniques in this investigation. The study's findings and the discussion that follows lead to the following conclusions: Different real-world adjustments have a minor impact on the idea of attitude change. The ease-of-use change has some bearing on behavioral goal change. Perceived value and ease of use have a simultaneous effect on intentions to modify behavior. Perceived value changes have no bearing whatsoever on changes in real usage. Recalling the ease of the change in use makes the change feel somewhat realistic. The intention to change one's behavior has some bearing on the actual usage. Perceived utility, perceived ease of use, and behavioral intentions all have an impact on how effectively change is used. Changes in perceived value have an impact on changes in actual consumption because they alter behavioral intentions. Changes in perceived ease of use have an impact on real changes in use when behavioral intentions are variable.